Avaliação do tratamento superficial com laser de CO2 ultrapulsado e sistema adesivo universal e envelhecimento de resinas compostas na resistência de união após reparo - Morais, Alexandre (2021)
The demand for aesthetic restorations has skyrocketed. Composite resins are the most suitable materials used for such reconstructions. They are used in direct, indirect or semi-direct techniques. Despite all the aesthetic advantage, adhesive technique, dissipation of tensions generated by chewing and conservative treatment, resins tend to suffer degradation over time, thus reducing their longevity. With the appearance of discoloration of the material, fracture or even wear, the professional is in doubt about the replacement or repair of this restoration. Replacement has always been the most used option. However, when there is a specific involvement of this problem without compromising the adhesive layer, the repair can be a biological and financial alternative. There is only the gluing of a new layer over the pre-existing restoration only in the region compromised by the failure, thus allowing the professional to practice Minimally Invasive Dentistry. Composite resin blocks were made where failures were simulated, and later the surfaces were prepared to receive the appropriate treatments. One group did not receive any treatment (Grr) and on its surface repairs were made to composite resin. In the Gar group, a universal adhesive + repair resin was applied. In the Gsa group, Silane + Universal adhesive + Repair resin was applied. In the Glsa group, laser CO2 + silane + universal adhesive + repair resin was applied. In the Gla group, CO2 laser + universal adhesive + repair resin was applied. In the Gls group, laser CO2 + silane + repair resin was applied. The specimens were sliced to obtain toothpicks for the microtensile test. The toothpicks were stored in distilled water at 37ºC for one year. After this period, the microtensile test of the specimens was performed. It was possible to conclude that the macromechanical treatment of the repair surface increases the bond strength of the repairs. The use of universal adhesives or silane bonding agents associated or not also contributes to the increase in the bond strength of repairs made with composite resin.